Diversity of the mountain flora of Central Asia with emphasis on alkaloid-producing plants - Tayjanov, Karimjan; Mamadalieva, Nilufar Z.; Wink, Michael (Diversity, 2017)
The mountains of Central Asia with 70 large and small mountain ranges represent species-rich plant biodiversity hotspots. Major mountains include Saur, Tarbagatai, Dzungarian Alatau, Tien Shan, Pamir-Alai and Kopet Dag. Because a range of altitudinal belts exists, the region is characterized by high biological diversity at ecosystem, species and population levels. In addition, the contact between Asian and Mediterranean flora in Central Asia has created unique plant communities. More than 8100 plant species have been recorded for the territory of Central Asia; about 5000-6000 of them grow in the mountains. The aim of this review is to summarize all the available data from 1930 to date on alkaloid-containing plants of the Central Asian mountains. In Saur 301 of a total of 661 species, in Tarbagatai 487 out of 1195, in Dzungarian Alatau 699 out of 1080, in Tien Shan 1177 out of 3251, in Pamir-Alai 1165 out of 3422 and in Kopet Dag 438 out of 1942 species produce alkaloids. The review also tabulates the individual alkaloids which were detected in the plants from the Central Asian mountains. Quite a large number of the mountain plants produce neurotoxic and cytotoxic alkaloids, indicating that a strong chemical defense is needed under the adverse environmental conditions of these mountains with presumably high pressure from herbivores.